DEALING WITH AGGRESSIVE BEHAVIOR: IMPLEMENTING A TOKEN ECONOMY FOR CHILDREN IN A LEARNING CONTEXT - Tria Ariani, Nyoman Wiraadi; I Gde Dhika Widarnandana (PRATAMA WIDYA : Jurnal Pendidikan Anak Usia Dini, 2025)
This study applied a behavior modification strategy using the token economy method to reduce aggressive behavior in children within the classroom. The primary objective of this intervention was to gradually decrease undesirable behaviors while promoting expected behaviors through a reinforcement system based on tokens, which could be exchanged for rewards preferred by the children. This study employed a single-case experimental design with an A-B-A' framework, consisting of three phases: baseline phase (A), intervention phase (B), and follow-up phase (A'). Data collection was conducted using the Aggressive Behavior Diagnosis instrument, observation, and semi-structured interviews. Data analysis was performed using within-condition analysis and between-condition analysis approaches. The results indicated that implementing behavior modification through the token economy method contributed to the development of more positive learning behaviors, where children were able to complete tasks independently without constant supervision from the teacher. These findings suggest that the token economy method is effective in reducing children's aggressive behavior during classroom learning activities.